SERVANT LEADERSHIP AS A PREDICTOR OF PSYCHOLOGICAL EMPOWERMENT AMONG OUTSOURSED EMPLOYEES - M. Yusril Ecatama Putra Putra; Umi Anugerah Izzati (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
Outsourced employees often face job uncertainty and limited organizational support, making psychological empowerment a crucial factor in enhancing their work experience. However, limited studies have specifically examined how servant leadership influences psychological empowerment in the context of outsourced employees, who are structurally more vulnerable than permanent staff. This study aims to analyze the effect of servant leadership on the psychological empowerment of outsourced employees. An explanatory quantitative approach was employed, with data collected through questionnaires from 89 outsourced employees selected using purposive sampling. The research instruments were developed based on the dimensions of servant leadership by Liden et al. and psychological empowerment by Spreitzer, and were tested using validity, reliability, and simple linear regression analyses at a 0.05 significance level. The results indicate that servant leadership has a positive and significant effect on psychological empowerment, as shown by a regression coefficient of 0.451 and a significance value of 0.000. These findings highlight the role of supportive and empowering leadership in strengthening employees’ sense of meaning, competence, and autonomy. This study offers practical implications for organizations to adopt more humanistic leadership approaches to enhance the psychological empowerment of outsourced employees.